Peran KPI Dalam Mendorong Kinerja Karyawan dan Produktivitas Organisasi - Sudaryanto Sudaryanto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
In the modern era full of competition, organizations are required to always innovate and improve their performance. Key Performance Indicator (KPI) is one of the main performance indicators used to measure and evaluate the achievements of individuals, teams and the organization as a whole. KPIs are used in various fields, including business, education, and government. This research aims to identify the role of KPIs in encouraging employee performance and organizational productivity. The research method used is a qualitative descriptive method through literature study. The research results show that KPI has a crucial role in encouraging employee performance and organizational productivity. KPIs can set clear direction, increase motivation and engagement, provide constructive feedback, encourage communication and collaboration, identify training and development needs, and increase accountability in the organization. Failure to implement or manage KPIs can have significant consequences in driving employee performance and organizational productivity in the modern era. In addition, there are several ideal strategies for using it effectively, including measurable and well-defined measurements.